STRATEGI KOPING KELUARGA DALAM MERAWAT ANGGOTA KELUARGA YANG MENGALAMI THALASSEMIA DI KLINIK THALASSEMIA DI KLINIK RUMAH SAKIT UMUM DAERAH KABUPATEN CIAMIS TAHUN 2019 - esti saraswati; aap apipudin; nur hidayat (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2020)
Thalassemia or called Mediterranean anemia is a hereditary disease that occurs due to a lack of red blood cells in the human body so that the production of hemoglobin decreases. Based on data from the thalassemia room at Ciamis District Hospital (2018), it shows that 2018 data is 199 people. Furthermore, the number of routine patients undergoing transfusion in December 2018 was 150people. The problem of thalassemia can affect a family and this will cause anxiety and will have an impact on thefamily both in terms of time, psychosocial economics and emocial. So that families need the right coping strategies to avoid bad behavior which can only reduce temporary stress.The purpose of this study was to determine family coping strategies in caring for family members who experience thalassemia in the thalassemia clinic in the ciamis district general hospital in 2019. The method in this study was descriptive. The population in this study were families of thalassemia sufferers who led clients to undergo transfusions at the Thalassemia Clinic in Ciamis District Hospital. The method of sampling in this study is incidental sampling, as many as 60 respondents. The results showed that family abilities in family coping strategies in caring for family members who experience thalassemia were obtained in the strategy of effective category relationships as many as 42 respondents (70%), effective cognitive strategies as many as 42 respondents(70.0%), effective communication strategies as many as 47 respondents (78.3%), effective social support strategy for 37 respondents (61.7%), effective spiritual strategy as many as 32 respondents (53.3). The conclusion of this study is that family coping strategies in caring for family members who have thalassemia have been effective, namely the effective category of 34 respondents (56.7%).